Effect of Thermal Annealing on Charge Transfer States and Charge Trapping in PCDTBT:PC70BM Solar Cells. (8th July 2015) - Constantinou, Iordania; Lai, Tzung‐Han; Hsu, Hsien‐Yi; Cheung, Sin‐Hang; Klump, Erik D.; Schanze, Kirk S.; So, Shu‐Kong; So, Franky
Abstract : The impact of thermal annealing on charge transfer (CT) states in poly[N‐9″‐hepta‐decanyl‐2, 7‐carbazole‐ alt ‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole)] (PCDTBT):[6, 6]‐phenyl C71 butyric acid methyl ester (PC70 BM) bulk heterojunction solar cells is analyzed. Thermal annealing is found to increase the effectiveness of the CT states, facilitating exciton dissociation and carrier generation. An increase in the concentration of deep traps due to annealing is presented using mid‐gap photothermal deflection spectroscopy, resulting in suboptimal overall device performance.